π-extended rigid triptycene-trisaroylenimidazoles as electron acceptors - Menke, Elisabeth H.; Lami, Vincent; Vaynzof, Yana; Mastalerz, Michael (Chemical communications, 2016)
Two soluble isomeric acceptor molecules based on a triptycene core, which is connected to three aroylenimidazole units are described. Due to the inherent threefold axis, the molecules are soluble and thus could be fully photophysically characterized in solution and film. Additionally, the preliminary results of these acceptors in organic photovoltaic devices with two different donor materials are reported.
First published 12 November 2015
Gesehen am 05.05.2020